2016
DOI: 10.1016/j.cognition.2016.02.005
|View full text |Cite|
|
Sign up to set email alerts
|

Instruction to forget lead to emotional devaluation

Abstract: These findings suggest that the Distractor Devaluation effect previously reported in the attention field can be generalized to memory. This is one the first studies to show an influence of memory processes, namely forgetting, on emotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…In a recent investigation we demonstrated that using active inhibition processes to prevent the recall of long-term memory representations (i.e., during a Think/No-think task) results in their affective devaluation . This result aligns with findings by Vivas et al (2016) who also showed devaluation following active inhibition that was applied during a directed forgetting paradigm. Collectively, these results suggest that active inhibitory processes result in affective devaluation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a recent investigation we demonstrated that using active inhibition processes to prevent the recall of long-term memory representations (i.e., during a Think/No-think task) results in their affective devaluation . This result aligns with findings by Vivas et al (2016) who also showed devaluation following active inhibition that was applied during a directed forgetting paradigm. Collectively, these results suggest that active inhibitory processes result in affective devaluation.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the differences between the Think/Nothink paradigm and the visual search paradigms used in previous studies, and despite having subjects ignore internal memory representations rather than external stimuli, our findings were strikingly similar to those of past distractor devaluation studies: We found that the ignored no-think items were disliked compared to baseline items. Vivas et al (2016) also observed a similar long-term memory effect using a directed-forgetting task to elicit inhibition of stimulus memories. The similarity of these findings in long-term memory tasks to past distractor devaluation effects in visual search raises a question: Is affective devaluation a fundamental property of inhibition, occurring regardless of what we ignore and how?…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Such evidence has accumulated across a variety of attention tasks that require participants to avoid interference from distractors, including those involving two-item target localization (Raymond et al, 2003), simple-feature and difficult-conjunction search , preview search (Fenske, Raymond, & Kunar, 2004), and central-target discriminations (Martiny-Huenger, . Affective devaluation also occurs for stimuli from which a motor-response has been withheld in Go/No-go (Kiss et al, 2008) and Stop-signal (Wessel & O'Doherty, 2014) tasks, and whenever a mental representation of the item is ignored in working memory (De Vito, Ferrey, Fenske, & Al-Aidroos, 2018) or is suppressed in long-term memory during Think/No-Think or item-based directed-forgetting (Vivas et al, 2016) tasks.…”
Section: Inhibition Leads To Stimulus Devaluationmentioning
confidence: 99%
“…Specifically, we examined whether a marker of inhibition-the distinctly negative affective evaluations that result from the inhibition of sensory stimuli (Raymond, Fenske, & Tavassoli, 2003), their representations in memory Vivas, Marful, Panagiotidou, & Bajo, 2016) or associated motor-responses (Fenske, Raymond, Kessler, Westoby, & Tipper, 2005;Kiss, Raymond, Westoby, Nobre, & Eimer, 2008)would be evident in the stimulus ratings of items that had just been maintained in visual working-memory in an accessory state. Finding affective devaluation of prior accessory items, relative to baseline and prior active items, would be consistent with the view that inhibition is used to reduce the activation of currently-irrelevant working-memory items in an accessory state below the activation level of the active memory representation.…”
Section: Introductionmentioning
confidence: 99%